2014
DOI: 10.3906/sag-1302-132
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of uveitis in a referral hospital in Turkey

Abstract: A series of (E) -3- (3-(2,3-dihydro-3-methyl-2-oxo-3 H -benzoxazole-6-yl)-1-phenyl-1 H -pyrazole-4-yl)acrylamides (7a-k) were synthesized and evaluated for their in vitro inhibitory activities on COX-1 and COX-2 isoforms using a human whole blood assay as well as their antiplatelet profile against human platelet aggregation using arachidonic acid as agonists. Among the synthesized derivatives 7a-k, especially compound 7g exhibited dual anti-inflammatory and antiplatelet activity with selective COX-2 inhibition. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 53 publications
(124 reference statements)
4
13
0
Order By: Relevance
“…This emphasizes the value of epidemiological studies to constantly update the working ophthalmologists with the most recent pattern of uveitis in their area. 4 , 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the value of epidemiological studies to constantly update the working ophthalmologists with the most recent pattern of uveitis in their area. 4 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…In this domain, a number of reports and studies have been published from different countries, in order to report and expose the predominant causes and forms of ocular inflammation in each country. [1][2][3][4][5][6] The present study aims to report the causes of uveitis among patients referred to a tertiary level hospital in Upper Egypt. a written informed consent at their first visit for collection of data from their medical records in epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Considering posterior uveitis, toxoplasmosis was the most common cause of it in these studies, while Behçet’s disease (BD) and idiopathic forms were the next most common causes of posterior uveitis in the Middle East and Europe, respectively [ 2 ]. However, in another study in Turkey that evaluated patients with all kinds of uveitis between 1990 and 2010 retrospectively, BD was the most common etiology ahead of idiopathic uveitis [ 3 ]. It seems that idiopathic uveitis represents 23–44% of the cases with uveitis in the studies conducted in the West, Iran, Saudi Arabia, and Japan [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 3000 consecutive patients with uveitis in the UK noted that 78% were in the 16–65 age group, 13% were under 16 years of age and 9% were over 65 years of age 6. Similarly, Çakar Özdal  et al reported that the mean age of presentation with uveitis was 36 years of age 7. With regard to gender, most but not all studies report a slight female preponderance 4 6–11.…”
Section: Epidemiologymentioning
confidence: 99%